2010
DOI: 10.1007/s10152-010-0217-0
|View full text |Cite
|
Sign up to set email alerts
|

The embryonic phase and its implication in the hatchling size and condition of Atlantic bobtail squid Sepiola atlantica

Abstract: Early life stages of cephalopods are somewhat complex due to the life history strategy or species specificity of generalized ontogenetic patterns and processes. This work aimed to determine the time length of embryonic development at different temperatures, and if the egg size is a determinant of hatchling size in Sepiola atlantica d 0 Orbigny, 1839-1842. Successful hatching occurred in 98.5-100% of the eggs for each female. As seen in other coleoid cephalopods, temperature determines the amount of time for em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
3
3
0
Order By: Relevance
“…Rodrigues et al 2009, Rodrigues et al 2010Jones & Richardson 2010). Moreover, the size of the smallest individuals of S. atlantica collected in Areamilla coincides with hatchling size observed by Rodrigues et al (2011).…”
Section: Discussionsupporting
confidence: 57%
“…Rodrigues et al 2009, Rodrigues et al 2010Jones & Richardson 2010). Moreover, the size of the smallest individuals of S. atlantica collected in Areamilla coincides with hatchling size observed by Rodrigues et al (2011).…”
Section: Discussionsupporting
confidence: 57%
“…These peaks match the maturity index peaks (MGSI and FGSI) found in the present study. Because the length of S. atlantica embryonic development is positively correlated with water temperature (Rodrigues et al 2011b), embryos could grow quickly (±23 days at 18°C) and hatch in the same season they were spawned, which would explain the correspondence between the peak of juvenile abundance (Rodrigues et al 2011c) and the maturity index peak found here.…”
Section: Discussionsupporting
confidence: 48%
“…In a study on spawning strategy, Rodrigues et al (2011a) found trade-offs between female ML and egg size and mass in S. atlantica; the present results are in agreement only with the relationship between ML and egg mass. Our analyses of the relationships between female ML and fecundity, female ML and the coefficient of variation of ripe oocyte mass, and female ML and egg mass suggest that larger females do not produce larger numbers of progeny, but larger females could contribute to the next generation with higher-quality hatchlings because of increased egg and hatchling size (see Rodrigues et al 2011b). Larger hatchlings are suggested to have better survival capabilities when compared with smaller hatchlings (Steer et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Given that the embryonic development lasts for 40-47 days on average (Villanueva et al, 2003), two peaks of hatchlings are expected around March and August. Regarding sepiolids, spawning occurs between March and July (Rodrigues et al, 2011a) with an early development lasting for around 62-23 days at 13-18°C (Rodrigues et al, 2011b) and hatching occurring between May and September (Rodrigues et al, 2012). In contrast, O. vulgaris has an extended embryonic development of up to 4 months (Mangold and Boletzky, 1973).…”
Section: Spatio-temporal Changes In Paralarval Abundancementioning
confidence: 99%